Synthesize and Investigate the Applicability of Carbon Dioxide Capture of Zeolite-based Geopolymer Materials - Dinh The Cuong; Nguyen Thi Truc Phuong; Nguyen Minh Phuoc; Lu Thanh Thien; Ngo Tran Hoang Duong; Nguyen Van Dung; Nguyen Quang Long (Chemical Engineering Transactions, 2023)
In today's world, people are facing the challenges of extreme weather events, global warming, and the rapid degradation of nature and the environment. One of the major contributors to these issues is the increased concentration of carbon dioxide (CO2), a greenhouse gas, in the atmosphere following the industrial revolution. In response to this crucial situation, this study focuses on the zeolite-based geopolymer material synthesis with various zeolite compositions. X-ray diffraction (XRD) analysis confirmed the retained structure of the powdery zeolite. These materials are designed to exhibit stability under various conditions and to investigate their capability to capture CO2 through gas flow. The study assesses the performance of these materials in capturing CO2, aiming to provide a foundation for the development of effective CO2 capture materials and the reduction of greenhouse gas emissions. The sample with zeolite X content of 45.6 wt% has a CO2 adsorption capacity of 21±1 mg/g with an inlet gas of 3 %v CO2 and remained almost same adsorption capacity after two times of heat regeneration.